Intellectual Capital And Cost Stickiness: A Modified Value Added Intellectual Coefficient (Mvaic) Approach - Dwi Irawan (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to provide empirical evidence about the relationship between intellectual capital and cost stickiness. Intellectual Capital has been widely studied about its effect on company performance, but still not much has been studied about its effect on cost behavior. Intellectual Capital in this study uses the Modified Value Added Intellectual Capital (MVAIC) approach. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017 - 2018. The sample in this study was 119 companies which were selected through purposive sampling. The results of this study indicate that the intellectual capital carried out by the company is able to reduce the level of cost stickiness in manufacturing companies in Indonesia. In practice, the IC carried out by the company is able to reduce cost stickiness, so that it can improve the financial performance of the firm.